Influence of plastic deformation in processes of agglomeration of the diamond hybrid material on structure and hardness of CVD-diamond - Shulzhenko, A.; Ashkinazi, E.; Sokolov, A.; Gargin, V.; Kotko, A.; Loshak, M.; Aleksandrova, L.; Tkach, V.; Romanko, L.; Ralchenko, V.; Konov, V. (Functional Materials, 2014)
Results of research of the "light" and "black" CVD diamond structure in hybrid material, which is the CVD diamond covered by polycrystalline diamond shell, are presented. Hardness of the initial CVD diamond and after high pressure-high temperature (HPHT) treatment is defined. Increase of hardness of the "black" CVD-diamond after HPHT-processing at 20 % was found. Electron microscopy was used to determine mechanism of the polycrystalline diamond compound shell binding with the CVD-diamond surface.